Enteric nervous system analyses: New biomarkers for environmental quality assessment - Pustiglione Marinsek, Gabriela [UNESP]; Moledo de Souza Abessa, Denis [UNESP]; Gusso-Choueri, Paloma Kachel [UNESP]; Brasil Choueri, Rodrigo; Nascimento Gonçalves, Alexandre Rodrigo [UNESP]; D'angelo Barroso, Beatriz Vivian [UNESP]; Souza Santos, Gustavo; Margarete Cestari, Marta; Galvão de Campos, Bruno [UNESP]; de Britto Mari, Renata [UNESP] (Elsevier, 2018)
The gastrointestinal tract (GIT) of fish is a target of contaminants since it can absorb these substances. We evaluated the morphophysiological alterations in the GIT of Sphoeroides testudineus collected in two estuaries presenting differences in their environmental quality (NIA and IA). The intestine was analyzed for histological and neuronal changes; liver and gills for biochemical markers; muscle tissues for neurotoxicity and peripheral blood for genotoxic damage. The results showed alterations in the GIT of the animals collected in the IA, such as muscle tunica and goblet cell density reduction, increased intraepithelial lymphocytes density and changes in neuronal density. Furthermore, changes were observed in MTs and LPO in the gills. Thus, we suggest that TGI is functioning as a barrier that responds to ingested contaminants, in order to reduce their absorption and translocation. Thus, alterations in morphophysiological and enteric neurons in S. testudineus can be used as biomarkers of environmental contamination.
Keywords: Acetylcholinesterase; Aquatic pollution; Fish; Myenteric plexus; Nitric oxide